Excellent Service Pattern for Customers at BRI Link in Makassar City - Maryadi, Maryadi (Pinisi Business Administration Review, 2023)
Excellent service patterns are one of the main elements in business that determine how a company or organization behaves in relation to the services provided to customers. Therefore, the aim of this research is to determine the pattern of excellent service at Bri Link for customers in Makassar City. This type of research is qualitative using a descriptive approach. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique used consists of data collection, data presentation, data condensation, and drawing conclusions. The research results show that the BRI Link excellent service pattern provided to customers has been running well, this can be seen from several indicators of excellent service patterns, namely attitude, attention, actions, abilities, appearance, and responsibility. Because providing excellent service to customers is very important. A company that is able to meet customer needs and desires will gain huge profits, both in the form of finances and reputation